Interrelations between Diabetes Therapy, Self-Monitoring of Blood Glucose, Blood Glucose and Non-fatal or Fatal Endpoints in Patients with Type 2 Diabetes - Schneider, Berthold; Martin, Stephan; Heinemann, Lutz; Lodwig, Volker; Kolb, Hubert (Arzneimittelforschung, 2007)
The ROSSO study is a retrospective, longitudinal cohort study performed to obtain epidemiological data on self-monitoring of blood glucose (SMBG) in patients with type 2 diabetes and to investigate the impact of SMBG on disease-related morbidity and mortality. 3,268 patients from 192 doctor’s practices in Germany were included and their data from diabetes diagnosis (between 1995 and end of 1999) till drop-out (120 died, 17 drop-outs) or end of 2003 were collected from the medical records. The mean observational time was 6.5 years; total patient years of follow-up were 21.266 years. Based on these population data, questions about the motivation of patients with type 2 diabetes to start with SMBG, the changes in diabetes therapy and blood glucose associated with SMBG and the relationship of SMBG with non-fatal or fatal events during follow-up were evaluated.Use of SMBG is significantly associated with personal and baseline conditions. Patients using SMBG are more frequently treated by an internist, more often male, have more frequently a private health insurance, exhibit less frequently arterial hypertension, are younger, have lower systolic blood pressure and higher values of fasting blood glucose (FBG), HbA1c and triglycerides at diagnosis. The start of SMBG is preceded by a steady increase in blood glucose levels. It is accompanied by an intensification of diabetes therapy and followed by a significant reduction of blood glucose in the year after start of SMBG. 67 % of the patients treated with diet only before SMBG began with antidiabetic medication concomitantly with SMBG (48 % with oral antidiabetic agents (OAD), 9 % with insulin and 10 % with OAD and insulin) and 30 % of the patients treated with OAD started on additional insulin treatment in parallel with SMBG. Switching from no antidiabetic medication to OAD reduced the mean FBG levels significantly from 9.31 to 8.70 mmol/l, from no medication to insulin from 10.05 to 6.93 mmol/l and from no medication
Keywords: Diabetes, type 2; ROSSO study, intensification of antidiabetic medication, reduction of blood glucose; reduction of non-fatal or fatal events, self-monitoring of blood glucose; Self-monitoring of blood glucose